Implantation of Polydioxonone (PDO) Threads Decreased Dorsolumbar Subcutaneous Fat Weight in Obese Female Rats (Rattus Norvegicus) - Diana Niti Santoso; Anak Agung Gde Putra Wiraguna; I Gusti Made Aman (Fakultas Kedokteran Universitas Udayana, 2021)
Introduction: Thread-lifts, especially using polydioxanone (PDO), are thought to have targeted lipolysis effect, but have never been empirically proven. The aim of this study was to prove that the implantation of polydioxonone (PDO) threads decrease dorsolumbar subcutaneous fat weight in obese female rats (Rattus norvegicus). Methods: This experimental study used posttest only control group design. The research subjects were 36 healthy Wistar rats, females, aged 16-18 weeks, obese with a body weight of 250-300 grams (Lee index criteria> 0.3). Obesity was induced by high-carbohydrate and high-fat feed. The rats were then divided into 2 groups, the negative control group with catgut thread implant treatment (P0) and the treatment group with polydioxonone (PDO) thread implant treatment (P1). After 28 days the rats were euthanized, skin tissue was collected, subcutaneous fat was searched and separated from the dorsolumbar depots found in the subcutaneous layer in the lumbar spine at the dorsal part of the body, then measured with the Sartorius brand scales. Results: The median weight of dorsolumbar subcutaneous fat in the P0 group was 1.05 (0.80; 1.90) grams, while in P1 group was 0.90 (0.70; 1.10) grams. The results of the comparative analysis with Mann Whitney test showed a p value of 0.016, which means that there was a difference in dorsolumbar subcutaneous fat between groups after 28 days. Conclusion: Implantation of polydioxonone (PDO) threads decreased dorsolumbar subcutaneous fat weight in obese female rats (Rattus norvegicus).